Pulsatilla chinensis (Bge.) Regel: A Systematic Review on Anticancer of Its Pharmacological Properties, Clinical Researches and Pharmacokinetic Studies - Li, Hang; Wang, Lilan; Zhang, Xiaojing; Xia, Wenxin; Zhou, Xirong; Sui, Hong; Fu, Xueyan (Frontiers in Oncology, 2022)
Pulsatilla chinensis (Bge.) Regel (PC) is one of the most commonly used Chinese medicines and has a history of thousands of years. This article reviews the research results of anti-cancer activity and its mechanism of action obtained from experimental, clinical, pharmacokinetic and bioinformatic studies in recent years. A large number of studies have shown that PC exerts had anti-cancer effects on different types of tumor cells by inhibiting cell proliferation, inducing apoptosis, inhibiting cell cycle and energy metabolism, inducing autophagy, and inhibiting angiogenesis. The literature has shown that PC can trigger the expression of autophagy-related molecules, activate the mitochondrial apoptotic pathway, inhibit the phosphorylation of PI3K downstream factors, down-regulate the expression of glycolysis-related proteins, and regulate a series of cancer-related signal pathways and proteins. The molecular mechanisms involved in PC include signal pathways such as Notch, PI3K/AKT/m TOR, AKT/mTOR, and MEK/ERK. The article also discusses the derivatives of the active ingredients in PC, which greatly improved the anti-cancer effect. In conclusion, this review provides a comprehensive overview of the biological effects and mechanisms of PC against cancer. The analysis of the literature shows that PC can be used as a potential drug candidate for the treatment of cancer.